Historical memory and national identity of Belarusians and Russians: experience of historical and sociological research - Kruchek, Petr S.; Rakachev, Vadim N.; Rakacheva, Yaroslava V.; Sergeev, Vsevolod N.; Astroga, Victor A. (Journal of the Belarusian State University. History, 2024)
Based on the results of a historical and sociological study conducted among student youth in Belarus and Russia, the specifics of the relationship between historical memory and collective identity are examined from different theoretical and methodological approaches. It is noted that Belarusian students have a strongly expressed ethnonational identity, their historical memory is concentrated on images of the national past, ideas of ethnocultural identity and state independence, and historical consciousness is aimed mainly at the near past and present. Among Russian students, the civic-state identity prevails; their historical consciousness is drawn to the distant past. It is concluded that the presence of a common history between the two peoples and the reflection of past events in the historical memory of Belarusian and Russian young people suggests that they have a single, predominantly retrospectively oriented, collective identity.
Keywords: historical memory; national identity; Belarus; Russia; collective memory; historical consciousness